Technology and Higher Education: A Bibliometric Analysis - Carmen Rodríguez Jiménez; Mariano Sanz Prieto; Santiago Alonso García (MDPI AG, 2019)
Technology in education is one of the current realities that generates most interest. The objective of this research is to analyze the scientific production of educational technology in the higher education stage, within the Web of Science database. To carry out this study, a bibliometric study was conducted, which first established the keywords that would govern the rest of the research and continued with the analysis of different variables that addressed different features, from the origin of the archives to the authors or the most prolific and relevant institutions in the scientific community. The results indicate that there has been a significant increase in publications on this subject in recent years, and as evident from the current peak, this is a growing trend that will lead to more research in the coming years.